Efek kombinasi vitamin B1, B6, B12 untuk menurunkan intensitas nyeri pada penderita neuropatik diabetes - Rizaldy Taslim Pinzon; Jesisca Jesisca (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2018)
Background: Neuropathy diabetic pain are common symptom in patient with diabetic melitus. The combination of vitamin B1, vitamin B6, and vitamin B12 usually used for treatment the pain, the result of previous studies are limited and conflicting.Objective: The aim of the study to measure the convering of intensity of pain in diabetic neuropathy.Method: The method of study using quase experimental design with pre and post treatment patient were selected by conservative sampling method from Bethesda Hospital, Yogyakarta. There are 68 patient diabetic neuropathy to follow in the study. Fact patient received combination of vitamin B1 100 mg, vitamin B6 100 mg, and vitamin B12 5000 mcg once a day for 3 month. Pain intensity measured using visual analog scale (VAS) on the first initial visited after 30th day and 90th day.Results: The 68 patient consist of 27 (39.7%) male and 41 (60.3%) women. The mean age 58.32±6.72 years. The mean duration of Diabetic 4.32±2.86 year. The study showed that the pain intensity lower significantly after received vitamin B (p<0.001). The mean pain intensity in first VAS 43.68±12.32 lower to 20.42±11.24 and in the end of study lower to 12.23±8.39.Conclusion: The combination of vitamin B1, B6, B12 significantly lower pain intensity of patient diabetic neuropathy.